OR15-03 High Prevalence of Gene Variants in Boys of Prepubertal Age with Clinical Suspicion of Central Hypogonadism and Low AMH - Brunello, Franco (J Endocr Soc, 2020)
Introduction: In boys of prepubertal age, the diagnosis of central hypogonadism may be difficult to ascertain since gonadotropins and testosterone are normally low. Sertoli cell markers, like AMH and inhibin B, may be useful. In recent years, with the development of next generation sequencing (NGS) technology, the number of genes associated with central hypogonadism has had an exponential increase. However, even with these advanced techniques, the gene variants with potential pathogenicity can be found at present in only 30-50% of the patients. Hypothesis of the study: Low serum AMH is an appropriate screening biomarker to select patients for NGS, in order to make a genetic diagnosis in boys of prepubertal age with suspected central hypogonadism. Patients and methods: All patients aged 1-10 yr referred between 2001 and 2018 with clinical suspicion of central hypogonadism (micropenis and cryptorchidism and/or microorchidism), with low serum AMH (<10(th) centile) were included. Serum AMH was determined by ELISA (Beckman-Coulter), and LH, FSH and testosterone (T) by ECLIA (Roche). NGS was performed with the TruSight™ One Sequencing Panel in a NextSeq® 500 sequencer (Illumina). Results are expressed as medians (range). Results: 13 patients were included. Age at first visit was 4.4 (0.1-9.2) yr. Cryptorchidism was present in all of them, micropenis in 10 and microorchidism in 11. Orchiopexy was required in 11 boys and the other 2 responded to hCG treatment. 4 patients had olfactory disturbances, 1 had sensory deafness and 1 had piebaldism. 2 patients had a family history of olfactory disturbances and/or central hypogonadism. 7 patients could be followed up to pubertal age, and the diagnosis of central hypogonadism was clinically confirmed. At age 6.1 yr (1.2-10), AMH was 159 pmol/L (65-363), LH was <0.1 IU/L in all, FSH was 0.61 IU/L (<0.1-1.9). 17 variants in 9 genes associated with central hypogonadism were found in 10 of 13 patients. 5 boys had 1 gene variant, while 4 had 2 gene variants and 1 had 3 gene variants indicating probable oligogenicity, in the following genes: FGFR1 (n:4), CHD7 (n:3), PROKR2 (n:2), SOX10 (n:2), AXL (n:2), HS6ST1 (n:1), AMHR2 (n:1), NSMF (n:1), DCC (n:1). Conclusion: A high prevalence of gene variants was found in boys of prepubertal age with a suspicion of central hypogonadism based on micropenis and cryptorchidism and/or microorchidism with low serum AMH.